Patriarchal Spell In Veronica Roth’s Divergent - Tesya Armelia; Rabbi Antaridha; Thiska Septa Maiza (LPPM Universitas Dharma Andalas, 2022)
Divergent is the first series of Divergent trilogy penned by Veronica Roth. As a work that tells a story about a supposedly strong female protagonist, the novel seems to uphold feminist values. However, upon a closer look, the pro-feminist worldview found in the novel operates merely on a cosmetic level. The long-standing patriarchal ideas about women still hold this novel captive, making it incapable of realizing its affirmative feminist aspirations. This study aims at proving that Divergent’s superficial pro-feminist stance is subverted by the underlying support it has for patriarchal ideas. The analysis is conducted by applying Margery Hourihan’s theory regarding three patriarchy’s archetypal conceptions about women—The Mother, Damsel-in-Distress, and The Witch. In gathering the data and conducting the analysis, this study employs qualitative methods. The result of this study shows that, while the novel appears to be a feminist fiction, it is still firmly grounded in patriarchal and misogynistic values that do not coincide with current feminist ideas about gender equality and female identity.